THE PLAINS CREE CONNECTIVE STONES THEORY: EARTH-SKY VERTEBRAL SPINES AND UMBILICAL CORDS (Canadian Journal of Native Studies, 2026)
Set within the context of a traditional Plains Cree sweat lodge ceremony,the connective stones theory is interpreted according to Cree cosmologiesof the Swampy (Ontario), Woodlands (Manitoba), and Plains(Alberta) Peoples that recognize parallel vertebral spines and umbilicalcords between the sky and earth worlds. I make a connection betweenthe human spine and five other-related forms of being: 7 stars constellations,12 thoracic and (12 x 2) ribs of a ceremonial sweat lodge frame, thefirst 5 hot rocks of a sweat lodge fire, the cradle (or pit) of the lodge, andthe sacred pipe. This theory utilizes Indigenous metaphor as a researchtool to explore concepts of interconnectivity, relationality, and communicationbetween earthly beings, human activities, and the cosmos. Everythingin the universe is made of stardust: bones of spinal columns,willow saplings, animals, and all other forms of beings of physical andspiritual states—all are considered asiniyak (stones) in the connectivestones theory.